1981
DOI: 10.1080/14443058109386826
|View full text |Cite
|
Sign up to set email alerts
|

Religion and disaster: Popular religious attitudes to disaster and death with special reference to the Mt. Kembla and Appin coal mine disasters∗

Abstract: To cite this article: Stuart Piggin (1981) Religion and disaster: Popular religious attitudes to disaster and death with special reference to the Mt. Kembla and Appin coal mine disasters , Journal of Australian Studies, 5:8, 54-63,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Praying positively improved their ability to cope by giving them the reassurance that every event is caused by God, a belief which provided them with the strength to face the event. This is in line with different studies showing that religious beliefs provide people with a sense of power, intrinsic self-worth, optimism, low level of depression and a feeling of control and safety (Ai et al , 2013; Fujiwara, 2013; Bradshaw and Ellison, 2010; Piggins, 1981). Overall, having a stronger belief in God contrasted with a fatalistic attitude and rather improved community efforts for both coping and recovery.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Praying positively improved their ability to cope by giving them the reassurance that every event is caused by God, a belief which provided them with the strength to face the event. This is in line with different studies showing that religious beliefs provide people with a sense of power, intrinsic self-worth, optimism, low level of depression and a feeling of control and safety (Ai et al , 2013; Fujiwara, 2013; Bradshaw and Ellison, 2010; Piggins, 1981). Overall, having a stronger belief in God contrasted with a fatalistic attitude and rather improved community efforts for both coping and recovery.…”
Section: Discussionsupporting
confidence: 91%
“…Various studies have increasingly emphasized the role of religion in disaster (Johakim and White, 2015; Gaillard, 2010; Gaillard and Texier, 2010; Schmuck, 2000; Chester, 2005; Gillard and Paton, 1999) but findings often diverge. Some researchers found that religion may foster positive re-evaluations of a disaster, protect individuals from suicidal tendency and give people a feeling of control and safety post-disaster (Zaumseil et al , 2014; Stratta et al , 2014; Fujiwara, 2013; Piggins, 1981). Other studies identified more negative aspects, including fatalistic views on risks and disasters, divisions in the community and rivalry between its members, as well as between a religious community and those who are not involved in religious practices within such community (Paradise, 2005; Fountain et al , 2015; Guarnacci, 2016).…”
Section: Introductionmentioning
confidence: 99%